Singing in the Nineteenth Century: Technical Innovations in Spanish Treatises - Morales-Villar, María del Coral (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In the 19th century, European doctors developed scientific studies on vocal technique and its artistic application. Singing professionals and amateurs wanted to learn about these new resources and discoveries on phonation, breathing and the latest interpretative trends. The aim of this research is to document through a descriptive methodology the main innovations in vocal technique presented in five Spanish singing treatises published in the second half of the 19th century. The incorporation of these advances had a direct influence on the teaching of singing.